Pelatihan Penggunaan Mendeley Reference Manager Bagi Mahasiswa UNAS PASIM Bandung - Sri Mulyeni; Rini Handayani; Nastiti Rizky Shiyammurti; Herlina Herlina; Dhea Adinda (Lembaga Pengembangan Kinerja Dosen, 2023)
student often face difficulties in compiling a bibliography for their academic papers. To avoid plagiarism, it is important to include a comprehensive list of references. The large number of references required in academic writing can make it challenging for some students to manually create a bibliography. To overcome this issue, there is an application called Mendeley that can facilitate the automatic generation of bibliographies. However, many students are still unfamiliar with how to use the Mendeley application, and some may not even be aware of its exixtence. Therefore, this training is organized with the aim of providing a comprehensive understanding to the general student population on how to use the Mendeley application effectively for automatic bibliography creation. The training aims to empower students to independently manage their references, with the hope of achieving maximum results, such as enhancing participants’ knowledge and understanding of using Mendeley, as well as improving their skills in utilizing the application for various types of academic writing, including final projects, journals and theses.